VLSI supply chain security risks and mitigation techniques: A survey - Liu, Bao; Qu, Gang (Integration (Amsterdam), 2016)
Hardware is the foundation of security and trust for any security system. However, recent study has revealed that hardware is subject to a number of security risks. Some of the most severe risks come from the VLSI supply chain. Such risks compromise the foundation of any existing security design. In this paper, we present a systematic survey on these security risks and their corresponding mitigation techniques. Categorization of security threats in VLSI development and supply chain.Evaluation of countermeasure techniques.Categorization of countermeasure techniques.Problem formulation or threat modeling for each countermeasure technique.